2020
DOI: 10.7861/clinmed.2020-0301
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin D deficiency increase the severity of COVID-19?

Abstract: The severity of coronavirus 2019 infection (COVID-19) is determined by the presence of pneumonia, severe acute respiratory distress syndrome (SARS-CoV-2), myocarditis, microvascular thrombosis and/or cytokine storms, all of which involve underlying inflammation. A principal defence against uncontrolled inflammation, and against viral infection in general, is provided by T regulatory lymphocytes (Tregs). Treg levels have been reported to be low in many COVID-19 patients and can be increased by vitamin D supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
175
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(205 citation statements)
references
References 15 publications
9
175
0
5
Order By: Relevance
“…Hence, low 25(OH)D level was identified as independently associated with the likelihood of COVID‐19 infection. This finding is in agreement with the results of other studies [5,7,9–15,19,30–42]. Further, reduced risk of acute respiratory tract infection following vitamin D supplementation has been reported [43,44].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Hence, low 25(OH)D level was identified as independently associated with the likelihood of COVID‐19 infection. This finding is in agreement with the results of other studies [5,7,9–15,19,30–42]. Further, reduced risk of acute respiratory tract infection following vitamin D supplementation has been reported [43,44].…”
Section: Discussionsupporting
confidence: 94%
“…Further, reduced risk of acute respiratory tract infection following vitamin D supplementation has been reported [43,44]. Notably, a recent study from the UK [31–33] that included 449 subjects (from the UK Biobank) with confirmed COVID‐19 infection did not find an association between vitamin D metabolite concentration and the risk of viral infections [45] as well as COVID‐19 infection [5,7,9‐15,19,30‐37,39‐42,46]. Particularly, the participants were recruited by UK Biobank in the period 2006–2010 [31–33].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency (25(OH)-vitamin D level < 20 ng/ml) has also been suggested as risk factor for COVID-19 infection [185] and may contribute to its severity through its association with increased proinflammatory cytokines [186]. The prevalence of vitamin D deficiency amongst older adults may be as high as 65% in some groups in the UK [173,187].…”
Section: Impaired Sleep Stress and Anxietymentioning
confidence: 99%
“…Vitamin D enhances the innate immune response while, paradoxically, protecting against excessive inflammation by suppressing TNFα and the cytokines (e.g., IL-6, IL-17) implicated in severe COVID-19, and elevating anti-inflammatory IL-10 (19,28,31,33,45,91,149,(160)(161)(162)(163)(164)(165)(166)(167)(168)(169). Many of the articles referenced here include detailed descriptions of the role of vitamin D in preventing a "cytokine storm" and several authors, including Meftahi et al, and Biesalski, added a series of cartoons to their papers to simplify the concept (167,168).…”
Section: How Vitamin D May Decrease Serious Covid-19-associated Complmentioning
confidence: 99%